The Influence of Organizational Climate on Innovative Work Behaviour - Etikariena, Arum; Kalimashada, Shanindya Bias Imaji (Jurnal Psikologi, 2021)
This study discusses about the effect of organization climate on innovative work behaviour. The respondents ofthis study were 124 employees who work in a mining company which implement innovation. This research wasa quantitative research and used Innovative Work Behaviour Scale by Janssen (2000) and Organizational ClimateMeasurement by Patterson et al. (2005). The data analysis technique used multiple regression analysis. The resultshowed that there was an influence of organizational climate on innovative behavior in the workplace by 12.1%,R2 = .121; F(1, 122) = 16,721, p < .05.The results also showed from the three dimensions of organizational climate,only two has significant effects, they are flexibility & innovation, t(120) = 2.433, p < .05, and outward focus,t(120) = 2.113, p < .05. Dimension which not significantly affect innovation work behaviour is reflexivity, t(120)= -.143, p = .886. The implications of this study can be considered by organizations to develop a supportiveorganizational climate so that employees feel comfortable to display innovative work behaviors and at the endwill ultimately have a positive impact for the organization.